Endoplasmic Reticulum Stress Responses in Intratumoral Immune Cells: Implications for Cancer Immunotherapy. Issue 2 (February 2019) - Song, Minkyung; Cubillos-Ruiz, Juan R.
Abstract : Protective anti-tumor immune responses are mediated by effector molecules that enable successful elimination of malignant cells. As the site where transmembrane and secreted proteins are generated, the endoplasmic reticulum (ER) of immune cells plays a key role in this process. Recent studies have indicated that adverse conditions within tumors perturb ER homeostasis in infiltrating immune cells, which can impede the development of effective anti-cancer immunity. Here, we describe how the tumor microenvironment induces ER stress in immune cells, and discuss the detrimental consequences of persistent ER stress responses in intratumoral immune populations. We also explore the concept of targeting ER stress responses to reinvigorate endogenous anti-tumor immunity and enhance the efficacy of various forms of cancer immunotherapy. Highlights: The tumor microenvironment can disturb the protein-folding capacity of the ER in infiltrating immune cells, thereby causing persistent ER stress. Severe ER stress responses in intratumoral leukocytes can cripple anticancer immunity in murine models of disease. Soluble factors from patient-derived cancer specimens can inhibit metabolic pathways and alter human T cell effector functions by inducing ER stress responses. Disabling ER stress sensors or controlling the UPR can enhance anti-tumor immune responses in certain preclinical models of cancer. Targeting ER stress-related components in immune cells may be useful for improving the efficacy of cancer immunotherapies, although further studies are warranted.